How pre-strain affects the chemo-torsional response of the intervertebral disc. (June 2020) - Derrouiche, Amil; Feki, Faten; Zaïri, Fahmi; Taktak, Rym; Moulart, Melissa; Qu, Zhengwei; Ismail, Jewan; Charfi, Slim; Haddar, Nader; Zaïri, Fahed
Abstract: Background: The role of the axial pre-strain on the torsional response of the intervertebral disc remains largely undefined. Moreover, the chemo-mechanical interactions in disc tissues are still unclear and corresponding data are rare in the literature. The paper deals with an in-vitro study of the pre-strain effect on the chemical sensitivity of the disc torsional response. Methods: Fifteen non-frozen 'motion segments' (two vertebrae and the intervening soft tissues) were extracted from the cervical spines of mature sheep. The motion segments were loaded in torsion at various saline concentrations and axial pre-strain levels in order to modulate the intradiscal pressure. After preconditioning with successive low-strain compressions at a magnitude of 0.1 mm (10 cycles at 0.05 mm/s), the motion segment was subjected to a cyclic torsion until a twisting level of 2 deg. at 0.05 deg./s while a constant axial pre-strain (in compression or in tension) is maintained, the saline concentration of the surrounding fluid bath being changed from hypo-osmotic condition to hyper-osmotic condition. Findings: Analysis of variance shows that the saline concentration influences the torsional response only when the motion segments are pre-compressed ( p  < .001) with significant differences between hypo-osmotic condition and hyper-osmotic condition. Interpretation: The combination of a compressive pre-strain with twisting amplifies the nucleus hydrostatic pressure on the annulus and the annulus collagen fibers tensions. The proteoglycans density increases with the compressive pre-strain and leads to higher chemical imbalances, which would explain the increase in chemical sensitivity of the disc torsional response. Highlights: In-vitro study of the intervertebral disc osmo-mechanical response under torsion. No significant osmolarity effect when the intervertebral disc is pre-tensioned. Significant osmolarity effect when the intervertebral disc is pre-compressed.